2020
DOI: 10.1111/aos.14545
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of myopic progression in Finnish and Singaporean children

Abstract: Purpose To compare 3‐year myopic progression between Finnish and Singaporean children. Methods Myopic progression was compared between 9‐year‐old (mean age 9.7 ± 0.4 years, n = 92) and 11‐year‐old (mean age 11.7 ± 0.4 years, n = 144) Finnish (Finnish RCT) children and Singaporean children matched by age and refraction (SCORMMatched, n = 403) and 7‐ to 8‐year‐old Singaporean children matched only by refraction (SCORM Young, n = 186). Spherical equivalent (SE) was between −0.50 and −3.00 D. Refraction with cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 39 publications
(65 reference statements)
1
31
3
Order By: Relevance
“… 32 In a recent study, age at baseline was the most significant factor contributing to the 3-year progression of myopia in both Singaporean and Finnish children. 33 Overall, our results seem to indicate that myopia progression can be determined by faster myopia progression at a younger age; however, age of myopia onset was not associated with 2-year myopia progression in our study. Further longitudinal studies on myopia progression from childhood to adulthood are necessary to uncover the link among age, age of myopia onset, and myopia progression.…”
Section: Discussioncontrasting
confidence: 56%
“… 32 In a recent study, age at baseline was the most significant factor contributing to the 3-year progression of myopia in both Singaporean and Finnish children. 33 Overall, our results seem to indicate that myopia progression can be determined by faster myopia progression at a younger age; however, age of myopia onset was not associated with 2-year myopia progression in our study. Further longitudinal studies on myopia progression from childhood to adulthood are necessary to uncover the link among age, age of myopia onset, and myopia progression.…”
Section: Discussioncontrasting
confidence: 56%
“…10,120 The effect of parental myopia on myopia in their offsprings may not be taken as proof for a genetic contribution to myopia, since the correlation might also be the result of a shared lifestyle 121 and their higher education. 71 However, parental myopia was associated with a greater risk of early-onset myopia in a recent study. 75 Cognitive functions and education.…”
Section: Personal Characteristicsmentioning
confidence: 89%
“…An early age of onset of myopia appears to be the strongest predictor of high myopia in both Asians and White children. [71][72][73][74] It was recently shown that parental myopia was associated with a greater risk of early-onset myopia in Asian, Hispanic, non-Hispanic white, and African American children. 75 In children younger than 6 years of age the prevalence of myopia is low.…”
Section: Prevalence Of Myopia Across Age Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is convincing evidence that the rate of myopia progression is related to age and possibly to existing level of myopia (e.g., Ref. [60]). Therefore, the use of progressive spectacle lenses having a moderate range of addition powers for myopia control in children and juveniles would only be moderately effective in the first year if applied for the first time to a 10-year-old who has already passed the half-way point on their march to high myopia (−5.0 D).…”
Section: Discussionmentioning
confidence: 99%